Effectiveness of adequate chicken egg white consumption on dyspnea degree and exacerbation incidence in stable COPD patients practicing strength and endurance exercises - Monica, Nanda S.; Tarigan, Amira P.; Pradana, Andika; Mutiara, Erna; Pandia, Pandiaman; Sinaga, Bintang YM.; Sihombing, Benny; Rhinsilva, Ella; Zulkarnain, Zulkarnain; Listyoko, Aditya S. (Narra J, 2023)
Lack of physical exercise and inadequate nutritional intake in chronic obstructive pulmonary disease (COPD) patients could lead to low muscle mass and function, which causes reduced respiratory function, increased incidence of exacerbations, exercise intolerance, increased visits to health facilities, and low health status. Therefore, physical exercise and good nutritional intake are the main foundations of a comprehensive pulmonary rehabilitation program for COPD patients. The aim of the study was to determine the effect of chicken egg white supplementation on dyspnea degree and the incidence of exacerbations in stable COPD patients who perform physical exercise independently at home. A quasi-experimental study was conducted in 38 stable COPD patients based on the Global Initiative for Chronic Lung Disease (GOLD) 2021 classification criteria. The patients were divided into two groups: the control group who did smartphone application-assisted physical exercises and the intervention group who did the same physical exercises plus chicken egg white supplementation for 12 weeks. Performed physical exercises included both strength and endurance training. The degree of dyspnea was assessed with modified Medical Research Council (mMRC) dyspnea scale and the incidence of exacerbations was assessed by direct interviews at the beginning and at the end of the intervention. A Fisher’s exact test was used to assess the association between the intervention with dyspnea degree and exacerbation incidence. In the intervention group, chicken egg white supplementation for 12 weeks lowered the dyspnea degree by 3.16 times than the control (relative risk 3.16 with p=0.001). Furthermore, the incidence of exacerbations was also reduced by 1.8 times compared to the control group (relative risk 1.8, p=0.001). This study highlights a significant improvement in dyspnea degree and exacerbation incidence in COPD patients with the combination of protein supplementation and physical exercise. Therefore, adding chicken egg white intake could be beneficial for stable COPD patients practicing physical exercises.